2020
DOI: 10.1111/pde.14318
|View full text |Cite
|
Sign up to set email alerts
|

A novel SPINK5 mutation and successful subcutaneous immunoglobulin replacement therapy in a child with Netherton syndrome

Abstract: We report a 2-year-old patient with Netherton syndrome presenting with generalized exfoliative erythroderma, ichthyosiform dermatitis, trichorrhexis invaginata, hypernatremic dehydration, failure to thrive, and recurrent respiratory infections. Molecular analysis of SPINK5 identified a novel mutation (c.1530CA). Our case report also verifies and supports the safety and efficacy of subcutaneous immunoglobulin substitution in chronic generalized skin disorders associated with primary immunodeficiencies such as N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Several case studies report immunoglobulin replacement therapy of NS patients (mainly newborns and children), the majority of them describing a remarkable clinical response with no major adverse effects [16,19,283,284].…”
Section: Immunoglobulin Replacement Therapymentioning
confidence: 99%
“…Several case studies report immunoglobulin replacement therapy of NS patients (mainly newborns and children), the majority of them describing a remarkable clinical response with no major adverse effects [16,19,283,284].…”
Section: Immunoglobulin Replacement Therapymentioning
confidence: 99%
“…Furthermore, a decrease in itch and infections, decrease in use of topical steroids, improvement of the quality of hair, and improvement in overall quality of life and functioning was reported (see Tables 1 , S2 ). Remarkably, in 5 children, aged between 4 months and 2 years, a significant increase in weight and height was noted ( 29 , 54 , 72 ). This effect might be attributed to a general improvement in NS symptoms, thereby enabling growth.…”
Section: Discussionmentioning
confidence: 96%
“…A previous review revealed improvements in 61% of AD patients treated with IVIG (Jolles, 2002). Previous studies have also reported subcutaneous immunoglobulin substitution (SCIg) was effective in some patients with NS and revealed that SCIg appeared to be a suitable and safe alternative in patients with generalized skin diseases associated with primary immunodeficiencies and difficult intravenous access (Zelieskova et al, 2020). Further understanding of the underlying pathophysiology of integumentary changes will lead to more effective treatment in NS.…”
Section: Discussionmentioning
confidence: 99%